Peer effects, unobserved factors and risk behaviours: an analysis of alcohol abuse and truancy among adolescents - Rosa Duarte; José-Julián Escario; José Alberto Molina (Institute for the Study of Labor (IZA), 2007)
The objective of this paper is to examine the factors which affect alcohol abuse and truancy among adolescents. We propose a new theoretical specification in which alcohol abuse and truancy appear as derived demands, given that they condition peer group and family acceptance, and we introduce unobserved individual effects that can influence both behaviours. Empirically, our paper develops an analysis where, after controlling for the existence of unobserved individual factors affecting both decisions, we test for peer influences. Our results first show evidence that alcohol abuse and truancy share unobserved factors affecting both decisions, and then confirm the existence of significant peer group influences on these two deviant behaviours
urn:nbn:de:101:1-2008042556
Keywords: 330; Alkoholkonsum; Bildungsverhalten; Jugendliche; Familiensoziologie; Spanien